Dynamic and electrophoretic light scattering measurements on microtubules at low concentrations. - Annitta George; Ernesto Alva; Lorenzo Brancaleon; Marcelo Marucho (PLoS ONE)
The accurate characterization of microtubules is essential for understanding their roles in various biological activities in eukaryotic cellular processes. In vitro, experimental data on these systems often need more details and information on sample preparation protocols and experimental techniques. This deficiency leads to unreproducible or contradictory outcomes. The use of diverse experimental methods and preparations yields different results of hydrodynamic and electro-mechanical properties, complicating the process of obtaining meaningful data and conclusive information. This article presents a robust and detailed protocol for performing dynamic light scattering (DLS) and electrophoretic light scattering (ELS) measurements on microtubules at low concentrations. This method ensures accurate and reproducible results on essential microtubule filament parameters such as the diffusion coefficient (D) and electrophoretic mobility (μ) from which other structures' hydrodynamics, electrical, and stability properties can be elucidated.